Circular Economy for Clothes Using Web and Mobile Technologies—A Systematic Review and a Taxonomy Proposal - Faria, Rui; Lopes, Inês; Pires, Ivan Miguel; Marques, Gonçalo; Fernandes, Solange; Garcia, Nuno M.; Lucas, José; Jevremović, Aleksandar; Zdravevski, Eftim; Trajkovikj, Vladimir (MDPI AG, 2020)
Nowadays, it is possible to buy clothing using online platforms, either by accessing online brand stores, general online stores or circular economy platforms. This paper presents a study on mobile applications that support online commerce for clothing, focusing on the review of the mobile applications with features that are characteristic of the circular economy paradigm. Findings include the fact that almost all the mobile applications analysed have pictures illustrative of the clothes and accessories that are available for trading as well as their brief description. Furthermore, this paper presents a study of various scientific articles about the circular economy of clothes and how it can be beneficial to the future of the environment. It is a junction with a Web platform for its growth and its disclosure. The paper builds conclusions upon the assumption that the circular economy is a growing business that is part of a sustainable development where the main goal is to reduce the environmental impact. The paper proposes the analysis of an innovative taxonomy of mobile applications about the circular economy.